Do banks appraise internal capital markets during credit shocks? Evidence from the Greek crisis - Avramidis, Panagiotis; Asimakopoulos, Ioannis; Malliaropulos, Dimitris; Travlos, Nickolaos G. (Journal of Financial Intermediation, 2021)
Using data of bank loans to Greek firms during the Greek crisis we provide evidence that affiliated firms, having access to the internal capital markets of their associated group, are less likely to default on their loans. Furthermore, banks require lower loan collateral coverage from affiliated firms and are less likely to downgrade the affiliates’ credit profile. Finally, banks are more likely to show forbearance to affiliated firms with non-performing loans. The results are consistent with the view that banks manage their relationships with firms in a business group jointly, as opposed to viewing each firm as an independent entity. Our findings also suggest that the value of risk sharing through internal capital markets increases when external financing is scarce.